Nghị quyết kỳ họp bất thường lần thứ nhất, Quốc hội khóa XV (Nghị quyết số: 46/2022/QH15) - Quốc hội (2022)
Toàn văn Nghị quyết kỳ họp bất thường lần thứ nhất, Quốc hội khóa XV (Nghị quyết số: 46/2022/QH15)